E-Services as a Part of Implementation of the Strategies for Computerization of the Country (Case Study of Zabierzów Commune) - Julia Gorzelany-Plesińska (Barometr Regionalny, 2013)
The information and communication society is becoming increasingly important due to the growing demands of civilization, which are entailed by the process of globalization. Currently, we are witnessing the development of e-services in public administration in Poland, in response to the strategy of informatization. Thus, the objective of this paper is to indicate the way an information and communication society can develop by the introduction of electronic public services. Based on research conducted in the Zabierzów Commune, an attempt is made to establish the level of the introduction of e-services at a local level.